If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7x + 10 + 8x = 7 + x + 3 Reorder the terms: 10 + -7x + 8x = 7 + x + 3 Combine like terms: -7x + 8x = 1x 10 + 1x = 7 + x + 3 Reorder the terms: 10 + 1x = 7 + 3 + x Combine like terms: 7 + 3 = 10 10 + 1x = 10 + x Add '-10' to each side of the equation. 10 + -10 + 1x = 10 + -10 + x Combine like terms: 10 + -10 = 0 0 + 1x = 10 + -10 + x 1x = 10 + -10 + x Combine like terms: 10 + -10 = 0 1x = 0 + x 1x = x Solving 1x = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 1x + -1x = x + -1x Combine like terms: 1x + -1x = 0 0 = x + -1x Combine like terms: x + -1x = 0 0 = 0 Simplifying 0 = 0 The solution to this equation could not be determined.
| -7+4x-3x=-19 | | 9(9x-3)= | | 0.05x+0.10(x+6)=2.40 | | -7+4x-3x=-29 | | -3x+10x-9=-30 | | 12x^2-18x-24=0 | | 18x+15y+4+10x-5y-8= | | N-8n=45 | | 0.265+0.75x=0.16 | | x-x*15=100 | | 5-9(g+18)=1-6g+3 | | .3x-1.2+.1x=.4 | | 3k+1=2k+8 | | 6m=4(0)-2 | | .5(6x+4)=5(2x-8) | | 5-4(g+18)=1-6g+3 | | 9x+3+x-8=5x-5 | | 6(2x-4)-3x=-6 | | 4x+2x-76=3x+11 | | Ix-3I+1=5 | | 0.05x+0.10(x+6)=2.35 | | 52(2(25)+15)=100x | | (x+6)(x)= | | .25(x+5)+.10=6.50 | | -16+-10= | | 6x+5-2x=-39 | | -20=-2x-x-2 | | x+y*0.15=100 | | 6a^4-5a^3+3a^4= | | 21x+21=42x+14 | | 120-120r=102 | | 3x=8-4z-y |